The impact of Covid-19 on global stock markets: an event study analysis - Hassan, Ali (2021)
The COVID-19 pandemic that began towards the end of 2019 can be considered as one of the biggest outbreaks the world has seen in the past century. The interruption to economic activity and the uncertainty to finding a vaccine or a cure for the virus has created unforeseen levels of panic uncertainty in the economy. These uncertainties among investors are translated into volatility in stock markets. The current study uses an event study analysis to see how investors react to certain events or announcements.